2017
DOI: 10.1017/s0047404517000744
|View full text |Cite
|
Sign up to set email alerts
|

Public discourses on multilingualism in the UK: Triangulating a corpus study with a sociolinguistic attitude survey

Abstract: This article investigates public discourses of multilingualism in Britain. In contrast to previous research focusing on specific languages or varieties of language, we examine multilingualism as a metalinguistic construct and are interested in what is frequently said about multilingualism, and how it is said. More specifically, we explore the extent to which media discourses are consonant or diverge from the attitudes of lay people. Media discourses are investigated using a corpus-assisted discourse-study appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The authors concluded that 'language policy arbiters as individuals have a disproportionate amount of impact on language policy and educational programmes (Johnson and Johnson 2015, 223), which can open or close spaces for additive bilingual education. Johnson and colleagues' work emphasises language policy as a multi-layered process taking place across multiple levels of educational contexts, sociolinguistic and sociocultural features, such as language beliefs and ideologies, public media and institutional documents about bi/multilingual speakers, have also been shown to influence policy decisions (Jaworska and Themistocleous 2018;Johnson and Freeman 2010). Johnson and Freeman (2010) employed ethnography of language policy to make connections between macro and micro policy, illustrating how educators infuse their beliefs about pupils' needs in their interpretations of evolving federal, state, and local language policies.…”
Section: Making Sense Of Educational Policies For Eal Learnersmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that 'language policy arbiters as individuals have a disproportionate amount of impact on language policy and educational programmes (Johnson and Johnson 2015, 223), which can open or close spaces for additive bilingual education. Johnson and colleagues' work emphasises language policy as a multi-layered process taking place across multiple levels of educational contexts, sociolinguistic and sociocultural features, such as language beliefs and ideologies, public media and institutional documents about bi/multilingual speakers, have also been shown to influence policy decisions (Jaworska and Themistocleous 2018;Johnson and Freeman 2010). Johnson and Freeman (2010) employed ethnography of language policy to make connections between macro and micro policy, illustrating how educators infuse their beliefs about pupils' needs in their interpretations of evolving federal, state, and local language policies.…”
Section: Making Sense Of Educational Policies For Eal Learnersmentioning
confidence: 99%
“…There is a perception that educational policy and provision for EAL students in England has been closely related to the political agenda of the various governing parties. With regard to this study, there has been a widespread concern that the current government's 'hostile migration policy', which conflates minority languages with negative views of migration (Jaworska and Themistocleous 2018), has influenced the introduction of the current language policy in schools, that explicitly requires schools to collect data relating to EAL pupils' nationality and country of birth (DfE 2017).…”
Section: Context Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, as Fairclough (1989: 54) notes, media effects are largely accumulative and are generally practiced through the repetition of particular ways of presenting information as well as particular ways of positioning the reader. In turn, Jaworska & Themistocleous (2018) proposed corpus-based analysis as a useful analytical tool to uncover patterns of repeated discourses in larger amounts of data. Hence, in the present study, we utilise corpus tools and methods to determine the most frequent keywords which appeared in the news articles concerning the air tragedy.…”
Section: A Multidisciplinary Studymentioning
confidence: 99%
“…Ample investigations have been conducted to explore spoken language in communities worldwide, focusing also on how people and media talk about multilingualism (Jaworska and Themistocleous 2018). Yet, less attention has been paid to the written language displayed in public spaces that surround us on a daily basis (Ben-Rafael, Shohamy and Barni 2010).…”
Section: Introductionmentioning
confidence: 99%